Gender-related differential item functioning in SweSAT verbal subtests: the role of extramural English activities in first and foreign language performance - Neagu, Teodora; Laukaityte, Inga (Frontiers in Education, 2025)
Standardized admission tests such as the Swedish Scholastic Aptitude Test (SweSAT) aim to ensure fairness in higher education selection by assessing verbal and quantitative skills. Previous research on the SweSAT indicates declining scores in the Swedish Reading subtest and improved scores in the English reading subtest. Gender differences are present, with males outperforming females on most SweSAT subtests–males often perform better on the multiple-choice format used in SweSAT, especially in English as a foreign language, while females typically perform better in school. Informal English exposure through Extramural English (EE) activities, such as digital gaming and reading, is associated with higher English proficiency, with males engaging more in gaming. However, EE impact on first-language proficiency alongside gender-related differences in test performance remains unclear. This study investigates how EE activities and item format contribute to gender-related performance differences in the SweSAT verbal subtests. A total of 5,230 SweSAT test-takers completed a questionnaire on their engagement in EE activities, focusing on reading and gaming. The SweSAT verbal items were examined using Mantel-Haenszel (MH) Differential Item Functioning (DIF) analyses to identify gender- and EE-related item biases. Results showed that gamers were more likely to be favored on English reading comprehension items, whereas non-gamers were favored on Swedish subtests. English items displayed DIF favoring frequent readers, whereas low-frequency readers were favored on some Swedish items. Male-favored DIF appeared mainly on English items, and females were favored on Swedish items. No consistent DIF patterns were linked to item format or word class across verbal items.